Multithreaded Algorithms for Lossless Intra Compression of Point Cloud Geometry Based on the Silhouette 3d Coder - Komatsu, Otho T.; Medeiros, Edil; Alves, Lucas M.; Peixoto, Eduardo (2023 IEEE International Conference on Image Processing (ICIP), 2023)
This paper evaluates a new implementation of our Silhouette 3D (S3D) coder for lossless compression of point cloud geometry, which yields up to 18% improvement on compression efficiency over our previously reported results. With this it offers competitive performance compared to the state-of-the-art MPEG G-PCC, outperforming it for some sequences. Additionally, we propose and analyze two multithreaded algorithms based on the S3D coder, namely S3D-Subtree (S3D-S) and S3D-Subtree + TopTree (S3D-ST). We evaluate the performance of these algorithms from 2 to 128 threads so that the user can select the best tradeoff for the desired application. As expected, parallelization decreases compression efficiency, but both S3D-S and S3D-ST show minor penalties for a small number of threads, and S3D-ST offers better compression efficiency when a larger number is used.